Towards a Practical Implementation of a Reasoner for Inconsistent Possibilistic Description Logic Programming Ontologies - Gómez, Sergio Alejandro (2016)
This work reports on our e orts to implement a practical reasoner based on Dung-style argumentation semantics for potentially inconsistent possibilistic ontologies. Our Java-based implementation targets a subset of the description logic programming fragment that we codify in a Racer-like syntax suitably adapted for representing certainty degrees of both axioms and assertions. We introduce our approach with a running example, discuss implementation issues and present time complexity results.